Mechatronic ski binding - Senner, V.; Hermann, A.; Carqueville, P. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
Electromechanical components have already arrived in the field of sports equipment, such as changing the suspension fork stiffness of a mountain bike at the push of a button from the handlebar. This chapter now goes one step further, namely towards an intelligent system that can analyse a complex situation and independently derive measures from it. Why this makes sense, how it can work and which components had to be developed for this is shown using the example of a visionary Alpine ski binding. At the same time, the basics of a technical control circuit will be taught and sensors that are important for sports will be presented, which can be worn directly on the body or integrated into the equipment.